2010
DOI: 10.1254/jphs.10028fp
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatin Inhibition of Vascular Endothelial Growth Factor– Stimulated Nitric Oxide Production in Endothelial Cells

Abstract: Abstract. Angiostatin (AS), a proteolytic fragment of plasminogen, is a potent antiangiogenic factor. It was reported that AS attenuates the vasodilatory response to vascular endothelial growth factor (VEGF) in isolated interventricular arterioles. Here, we investigated the effect of AS on nitric oxide (NO) production in human umbilical vein endothelial cells (HUVECs). AS inhibited VEGF-stimulated NO production in a dose-dependent manner, whereas AS alone did not affect basal NO production. Disruption of kring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…47 Moreover, VEGF stimulates production of NO. 48 In addition, VEGF expression is increased by ALK-1 in vitro. 33 In this study, we demonstrated that cholesterol administration reduces endoglin/ALK-1/ VEGF expression in the murine aorta and increases atherosclerotic plaque size, which suggests that cholesterol might affect NO production by affecting of this pathway and thus STRASKY Z et al…”
Section: Discussionmentioning
confidence: 99%
“…47 Moreover, VEGF stimulates production of NO. 48 In addition, VEGF expression is increased by ALK-1 in vitro. 33 In this study, we demonstrated that cholesterol administration reduces endoglin/ALK-1/ VEGF expression in the murine aorta and increases atherosclerotic plaque size, which suggests that cholesterol might affect NO production by affecting of this pathway and thus STRASKY Z et al…”
Section: Discussionmentioning
confidence: 99%
“…Angiostatin is a MMP-induced proteolytic cleavage product of plasminogen that is capable of inhibiting angiogenesis, promoting apoptosis of endothelial cells, and disrupting capillary integrity leading to capillary dropout (6). Angiostatin is a potent inhibitor of VEGF and downstream mediators (146,161), has been shown to be persistently elevated after ischemic renal injury, and can significantly reduce VEGF-induced proliferation and repair of peritubular capillaries, consequently accelerating tubular and interstitial damage (110). Another potent extracellular antiangiogenic factors and inhibitors of cell proliferation that are highly expressed in the kidney is endostatin.…”
Section: Rarefaction: Definition MV Rarefaction and The Kidneymentioning
confidence: 99%
“…However, although we have shown that such factors are also upregulated in the stenotic kidney (10,11,15), their increase is accompanied not only by marked fibrosis, but also a significant MV rarefaction. The accumulation of extracellular matrix in the fibrotic kidney not only represents a buildup of scar tissue, but also generates an active source of potential antiangiogenic mediators, such as angiostatin, a potent inhibitor of VEGF and downstream mediators (65,75). Angiostatin has been shown to be persistently elevated after ischemic renal injury and can significantly reduce VEGF-induced proliferation and repair of peritubular capillaries, hence accelerating tubular and interstitial damage (52).…”
Section: Fibrosismentioning
confidence: 99%